Simulation and Modelling of Electrical Insulation Weaknesses in Electrical Equipment - Albarracín Sánchez, Ricardo (IntechOpen, 2018)
Around 80% of electrical consumption in an industrialised society is used by machinery and electrical drives. Therefore, it is key to have reliable grids that feed these electrical assets. Consequently, it is necessary to carry out pre-commissioning tests of their insulation systems and, in some cases, to implement an online condition monitoring and trending analysis of key variables, such as partial discharges and temperature, among others. Because the tests carried out for analysing the dielectric behaviour of insulation systems are commonly standardised, it is of interest to have tools that simulate the real behaviour of those and their weaknesses to prevent electrical breakdowns. The aim of this book is to provide the reader with models for electrical insulation systems diagnosis.